Landasan dan Pentingnya Pendidikan Kewarganegaraan di Institusi Pendidikan Tinggi - Muhammad Habib Pasaribu; Siska Lailan Munira; Sasmi Nelwati (Lembaga Pengembangan Kinerja Dosen, 2024)
Citizenship Education in higher education institutions plays a crucial role in shaping students' character as responsible and contributive citizens. This article discusses the fundamental concepts, history, foundations, urgency, and goals of CE in universities. CE focuses on character formation, Indonesian identity, national pride, and love for the homeland. The history of Citizenship Education dates back to 1957 with the introduction of civics. The foundations of CE encompass philosophical, juridical, and sociological aspects. The urgency of CE lies in fostering critical thinking and preparing the youth for the future. The objective of CE is to equip students with the knowledge, skills, and attitudes necessary to become active and responsible citizens.